Absolute chronology of Black Wheel Made Ware in the southern Levant and its synchronization with the northern Levant. (4th May 2021) - Lev, Ron; Bechar, Shlomit; Covello-Paran, Karen; Boaretto, Elisabetta
Abstract : Black Wheel Made Ware (BWMW) is a distinguished pottery-type of the Intermediate Bronze Age (EB IV) in the Levant, a period dated to the second half of the 3rd millennium BCE. Considerable research was done both on the origin of BWMW and on how these vessels reflect inter-regional relations. This paper presents the first radiocarbon-based absolute dating of BWMW contexts, sampled from a few sites in northern Israel. These 14 C dates clearly point to the 23rd century BCE as the period when BWMW was a circulated commodity in the southern Levant. Pottery types that are commonly found together with BWMW are potential candidates for the same chronological horizon. BWMW examples found in the northern Levant have no associated absolute dates and are assigned in general to the EB IVB period. Thus, the new dates presented here are, currently, the only secure absolute dating of BWMW pottery and should be used to revisit the absolute chronology of northern Levant sites where BWMW pottery has been identified.